Artisanal Petroleum Refining and Occupational Dynamics in the Niger Delta Region, Nigeria - J.L. Igben (Journal of Applied Sciences and Environmental Management, 2021)
This study examines the occupational dynamics of the population as a result of artisanal refining of crude oil in the Niger Delta using structured questionnaire administered to 240 household heads selected from two settlements, one far from area of artisanal refineries (controlled settlement) and the other in area of artisanal refineries (experimental settlement). The questionnaire covered location and demographic characteristics of the respondents, as well as the typology of occupations. The pair-wise Student t-test and simple percentages were used to analyse the data collected. The study revealed that there were significant dynamics (t = -0.22, df =12, p<0.05) in the number of respondents in identified occupational typologies as indirect impact of artisanal refining in the experimental and controlled settlements. The study recommends the intensification of efforts to implement existing laws on environmental protection and provision of employment for teeming population.